Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can someone give me a hint how to evaluate $$ \binom{n}{0}+\binom{n}{2}+\cdots+\binom{n}{o(n)},$$ where $o(n)$ is $n$ if $n$ is even and $n-1$ otherwise ?

share|cite|improve this question
up vote 3 down vote accepted

Consider: $$ \sum_{k=0}^n \binom{n}{k} x^k = (1+x)^n $$ Now you are computing: $$ \sum_{m \geqslant 0, n \geqslant 2 m } \binom{n}{2m} = \sum_{k=0}^n \binom{n}{k} \frac{1+(-1)^k}{2} = \frac{(1+1)^n + (1-1)^n}{2} = \frac{2^n + \delta_{n,0}}{2} $$

share|cite|improve this answer

We simply need to show the following two things: $$\sum_{i=0}^n \binom{n}{i} = 2^n$$ $$\sum_{i=0}^n (-1)^i\binom{n}{i} = 0$$

Both of these follow from the binomial formula. The result then follows routinely.

share|cite|improve this answer

if n is odd then consider the below series:$$ \binom{n}{0}+\binom{n}{1}+\cdots+\binom{n}{n} = 2^n$$ and we know that $$ \binom{n}{k} = \binom{n}{n-k}$$ so $$ \binom{n}{0} = \binom{n}{n} , \binom{n}{2} = \binom{n}{n-2} , ...$$ so for odd number the answer is $2^{n-1}$.

and for even number you can do the same thing like odd numbers.

share|cite|improve this answer

If you calculate the first few examples, you'll see a very clear pattern-- if you haven't already done this, that's where you should start.

Now to prove this pattern and other patterns within the binomial coefficients, it's very helpful to use the fact that the binomial coefficient $\binom{n}{i}$ is just the coefficient of $x^iy^{n-i}$ in $(x+y)^n$.

You can prove that the sum $\binom{n}{0} + \binom{n}{1} + \binom{n}{2} + \ldots + \binom{n}{n}=2^n$ just by setting $x=1$ and $y=1$ in the formula above to get $(1+1)^n$.

You can prove that the alternating sum $\binom{n}{0} - \binom{n}{1} + \binom{n}{2} - \ldots +(-1)^n \binom{n}{n}=0$ just by setting $x=1$ and $y=-1$ in the formula above to get $(1-1)^n$.

Now what happens if you add these two sums together?

share|cite|improve this answer

We have a group of $n$ people, where $n\ge 1$. The $n$-th person is George. The expression $$ \binom{n}{0}+\binom{n}{2}+\cdots+\binom{n}{o(n)}$$ counts the number of ways to choose an even number of people from our group (including the possibility of choosing $0$ people).

Pick any set $S$ of people from the first $n-1$. If $S$ has an odd number of people, add George. If $S$ has an even number of people, leave George out.

We can thus see that there are just as many ways to choose an even number of people from $n$ people as there are ways to choose a set of people from $n-1$ people.

But this number is $2^{n-1}$, for in choosing people from the first $n-1$, for every person we have $2$ choices, yes or no.

Note that $n=0$ is an exception to the rule we have found, for $\binom{0}{0}=1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.